2019
DOI: 10.1111/jpn.13214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary digestible lysine level on growth performance, blood metabolites and meat quality of broilers 23–38 days of age

Abstract: This study was done to evaluate the effects of different dietary digestible lysine (dig Lys) levels on growth performance, blood metabolites, carcass and breast yield, and breast meat quality of broilers 23–38 days of age. Three hundred 23‐day‐old Cobb‐500 male broiler chickens were allocated to a completely randomized design with five treatments (finisher diet containing 0.88%, 0.94%, 1.00%, 1.06% and 1.12% dig Lys) and six replicates of 10 birds each. Feed intake (FI) was not affected by different dietary di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…Contrary to the observations of the present study, Ghazanfari et al (2010) observed that in broilers that incremental changes in dietary protein levels did increase feed intake and improved weight gain and feed conversion, compared with a low level of protein in the diet. Jafarnejad et al Improved productive performance of broiler chickens has been observed when increased over NRC recommendation the levels of lysine (Oliveira et al, 2013;Bernal et al, 2014;Quadros et al, 2019;Zarghi et al, 2020) and methionine plus cystine (Goulart et al, 2011). In the current study, the increase in crude protein increased the lysine concentration in the diets over the NRC recommendations; however, the crude protein increase in diets did not have evident increase on the levels methionine plus cystine in the used diets over the NRC recommendations.…”
Section: Growth Performancecontrasting
confidence: 47%
See 1 more Smart Citation
“…Contrary to the observations of the present study, Ghazanfari et al (2010) observed that in broilers that incremental changes in dietary protein levels did increase feed intake and improved weight gain and feed conversion, compared with a low level of protein in the diet. Jafarnejad et al Improved productive performance of broiler chickens has been observed when increased over NRC recommendation the levels of lysine (Oliveira et al, 2013;Bernal et al, 2014;Quadros et al, 2019;Zarghi et al, 2020) and methionine plus cystine (Goulart et al, 2011). In the current study, the increase in crude protein increased the lysine concentration in the diets over the NRC recommendations; however, the crude protein increase in diets did not have evident increase on the levels methionine plus cystine in the used diets over the NRC recommendations.…”
Section: Growth Performancecontrasting
confidence: 47%
“…higher lysine levels than NRC recommendations promoted breast meat yield (Bernal et al, 2014;Zarghi et al, 2020). In the current study all diets were supplemented with the same lysine level and covered the NRC recommendation and the increase in CP level in diets had small increases in lysine or methionine plus cystine.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…The carcases were eviscerated manually and obtained by removing the head, feathers, feet, visceral organs, and gastrointestinal tract. The whole carcase was weighed and cut according to the procedure (Zarghi et al 2020a). Carcases and cut organs weighed by a digital weighing scale (0.01 g, model GF 400, A&D Weighing).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Dietary protein and amino acids (AAs) levels play a vital role in poultry nutrition to improve growth performance and animal welfare (Zarghi et al 2020a). The efficient utilisation of protein in the diet depends on the amount, composition, and digestibility of dietary AAs (Akbari Moghaddam Kakhki et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After bleeding, the carcase was obtained by removing, feathers, feet, skin and visceral organs. Weight of the carcase and part (breast, legs and frame defined carcase without the breast and legs) yield and abdominal fat were expressed as a percentage of live body weight (Zarghi et al 2020). In order to measure molecular concentrations of energetic metabolites in heart and breast muscles, about 1 g of heart and breast (1.5 cm deep in the right pectorals tissue) muscle were collected and wrapped in an aluminium foil and kept in À80 C freezer for later (determined ATP, ADP, AMP, PCr and CrN concentration) analysis (Tabatabaei Yazdi et al 2017).…”
Section: Slaughter and Sampling Proceduresmentioning
confidence: 99%